Design of Smart Electronic Component Tester Using ATMEGA 328P Microcontroller at Lubuklinggau State Vocational High School 3 - Novi Lestari (Institut Bakti Nusantara, 2019)
Today Microcontroller continues to grow very rapidly and is very much in demand in the field of control system applications. Even now there are many microcontrollers that have become modules. One of the widely used microcontroller modules is Arduino. Arduino is a type of board that contains a microcontroller. Multimeters that are usually sold in the market are mostly only for measuring current, voltage, and resistance of an electronic component and cannot measure the poles of each of these components so students must learn more about which poles are the components. This certainly becomes a problem for students who will assemble an electronic component. Therefore, it is needed a measuring device that does not only measure the amount of current, voltage, and resistance of a component, but also can know the poles and legs like diode and transistor components. This can be realized by designing a Smart Tester can measure the legs of electronic components. By using a microcontroller. The measurement data for each component will be displayed via LCD Display.